Pengaruh Fintech Dan Self Control Terhadap Pengelolaan Keuangan Dimoderasi Literasi Keuangan - Mayasari, Eka; Trisnaningsih, Sri; Priono, Hero (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
This study aims to analyze the influence of fintech and self-control on financial management among MSMEs in West Surabaya, as well as to examine the moderating role of financial literacy in this relationship. With the rapid development of fintech, many MSME actors are utilizing fintech to optimize their financial management. However, the effectiveness of fintech usage is influenced by the level of financial literacy among MSME actors. This research employs a quantitative approach with purposive sampling technique. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method via the SmartPLS 4 application. The results of the study show that both fintech and self-control have a positive and significant impact on financial management. Financial literacy was found to significantly moderate the relationship between fintech and financial management, but it does not moderate the relationship between self-control and financial management. This study contributes to the development of MSME financial management strategies in the digital era and provides important insights into the importance of financial literacy in optimizing the use of fintech